The most prominent social concepts when Lubon (Journal of the College of Basic Education, 2023)
Gustave Le Bon is a French sociologist, philosopher and physician.They specialized in studying several sciences and fields of knowledge at the same time, and were ahead of their time in explaining manyOf the phenomena, which he placed in frameworks and laws that show the validity of many of them later.He studied peoples' civilizations, their behaviour, customs and beliefs, and his studies are among the first of theseStudies, as he wrote about many civilizations of the East, and what helped him in that were his many trips.and frequent references to the places where these civilizations emerged, as well as his deepening in the study of the science ofPsychological sociology and his intellectual dissertations in this field enabled him to apply the theories of thisScience in the study of these civilizations, as well as a node of comparison between their societies in the pastAnd the present, and this is what distinguished his writings, as they were written in the spirit of the sociologist and the philosopher.He was very interested in studying the behavior of the groups, their reactions and the revolutions that resulted from them.We have divided this study into three sections.The first topic included Le Bon's most prominent scientific works, which he wrote during his scientific career.Distributed in various disciplines, and we will review most of these publications and the importance of each one.of them.As for the second topic, we will deal with the elements of civilization according to Lubon, which were represented by six elements.We will explain them as they appear in his writings and we will comment on them.In the third topic, we will discuss the collective behavior of Le Bon and the most important opinions that he came up with in this topic.The field and its analysis of this social phenomenon and the results that result from it.We also discussed the most prominent criticisms of Le Bon's theory of collective behavior.